Contribution of San Fernando in the fight against violence: a review - Garmendia Lorena, Fausto (2014)
San Fernando Faculty of Medicine of the Universidad Nacional Mayor de San Marcos began activities against violence in March 2003.Initial efforts were directed to organization of a working nucleus and collecting information on health consequences of political violence occurred in Peru during years 1980 to 2000. In this paper a historical review is presented on the beginnings, arduous organization and capacitation processes and results obtained in training of health professionals and university professors for a comprehensive health care of violence victims in regions that suffered the political violence as well as other achievements in innovation, creativity and trasference of knowledge for the process sustainability.